Returns to private education in Peru - Sebastián Calónico; Hugo \~Nopo (Inter-American Development Bank, Research Department, 2007)
The private provision of educational services has been representing an increasing fraction of the Peruvian schooling system, especially in recent last decades. While there have been many claims about the differences in quality between private and public schools, there is no complete assessment of the different impacts of these two type of providers on the labor markets. This paper attempts to provide such a comprehensive overview by exploring private-public differences in the individual returns to education in Urban Peru. Exploiting a rich pair of data sets (ENNIV 1997 and 2000) that include questions on type of education (public vs. private) for each educational level (primary, secondary, technical tertiary and university tertiary) to a representative sample of adults, this paper measures the differences in labor earnings for all possible educational trajectories. The results indicate higher returns to education for those who attended private schools than those who attended the public system. Nonetheless, these higher returns also show higher dispersion, reflecting wider quality heterogeneity within the private system. The private-public differences in returns are more pronounced at the secondary than at any other educational level. On the other hand, the private-public differences in returns from technical education are almost nonexistent. A cohort approach paired with a rolling-windows technique allows us to capture generational evolutions of the private-public differences. The results indicate that these differences have been increasing during the last two decades.
Keywords: J31; I2; 330; Returns to schooling; wages; Bildungsertrag; Privatschule; Allgemeinbildende Schule; Peru